Pengembangan Bahan Ajar Bahasa Indonesia untuk Penutur Asing (BIPA) berdasarkan Hasil Analisis Kebutuhan Belajar - Suyitno, Imam (Wacana, Journal of the Humanities of Indonesia, 2007)
Teaching Indonesian for Foreign Learners or Indonesian as a Foreign Language (IFL) is different from teaching Indonesian as a first language. The differences are due to the characteristics of the learners. IFL learners generally are adults who have language and cultural background and learning style different from those Indonesian learners have. These differences demand IFL teachers and instructors to prepare teaching-learning materials and the activities of the teaching-learning process in the classroom that are relevant to the learners' needs. Understanding the entry level behavior of the learners, the teaching materials, the teaching-learning approach, and the evalution process is of crucial importance in order to fulfill their needs. Learning needs analysis of IFL learners is also a prerequisite to developing adequate teaching-learning materials of IFL.